Distribution probability functions for models applied to hydraulic works in urban areas: LOG-GUMBEL vs LOG-PEARSON IIIRaúl - Raúl Montes-Pajuelo; Ángel Mariano Rodríguez-Pérez; Julio José Caparrós-Mancera; César Antonio Rodríguez-González (Anales de Edificación)
Hydrometeorological models for hydraulic design rely on probability functions to model extreme rainfall. This study compares Log-Gumbel and Log-Pearson III functions using data from Almodóvar reservoir (Cádiz). Log-Gumbel, a variation of the Gumbel distribution, yields higher, safer estimates for long return periods (T), but is highly sensitive to data changes. Log-Pearson III, widely used and more stable, shows consistent results despite data variability. For designs with limited or variable data—common in hydraulic works—Log-Pearson III is preferred. However, for urban drainage where safety is prioritized over stability, Log-Gumbel offers a conservative alternative for high T values.